(untitled) (Journal of EAHIL, 2019)
As medical librarians and information professionals we are familiar with the role of art in our work, through the atlases that line our bookshelves and the illustrations that routinely appear in both printed and digital literature. Why is this role important? There’s a clue in the familiar aphorism “A picture is worth a thousand words”, which captures the essential truth that art is about communicating information. Since our professional role is also the business of communicating information, there should be obvious benefits for us in studying and understanding how art performs this function.